2015
DOI: 10.7326/m15-1813
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Benefits and Harms of Antidepressant, Psychological, Complementary, and Exercise Treatments for Major Depression: An Evidence Report for a Clinical Practice Guideline From the American College of Physicians

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 74 publications
2
65
0
5
Order By: Relevance
“…The same authors recently published a similar review3 using the same data, but reported slightly different results by using different approaches for random effects meta-analysis. While the current study used the DerSimonian and Laird models, the recent study applied the restricted maximum likelihood models.…”
Section: Limitationsmentioning
confidence: 99%
“…The same authors recently published a similar review3 using the same data, but reported slightly different results by using different approaches for random effects meta-analysis. While the current study used the DerSimonian and Laird models, the recent study applied the restricted maximum likelihood models.…”
Section: Limitationsmentioning
confidence: 99%
“…Probably more than for other health conditions, comparative benefits of exercise and pharmacologic treatments have been examined and discussed in relation to depression (e.g., Stubbs et al, 2015; Gartlehner et al, 2016). According to the WHO (World Health Organization), depression is the leading cause of disability worldwide (WHO, 2016 http://www.who.int/mediacentre/factsheets/fs369/en/).…”
Section: Introductionmentioning
confidence: 99%
“…However, many patients do not respond to antidepressant medications, or experience side effects (Gartlehner et al, 2016). In addition, increasing evidence indicated a large placebo response, making it more challenging for novel medications to demonstrate their effectiveness (Rutherford et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Den avgjørende faktoren for behandlingseffekt er altså ikke hvorvidt medikamentet modifiserer eller endrer transmitterfunksjonen i hjernen, men om pasienten har troen på at behandlingen virker (4). Teorien om at positiv forventning øker effekten av antidepressiva støttes blant annet av en analyse på over 16 000 deprimerte pasienter (5).…”
unclassified